Modeling of fiberglass degradation process under stresses and alkaline environment - R.A. Kayumov; I.Z. Mukhamedova; B.F. Tazyukov (Учёные записки Казанского университета: Серия Физико-математические науки)
The constitutive relations for fiberglass were obtained. New methods were developed to analyze its behavior as microdamage accumulates and under the exposure to an aggressive alkaline environment. A finite element model was built to assess the stress-strain state of a fiberglass panel for predicting its durability in response to stresses and an alkaline environment. The convergence of the solutions was studied depending on the number of finite elements and the time step. The behavior of a fiberglass panel was analyzed with and without considering its deformations. The results show that the damage accumulated in a fiberglass panel must be taken into account to improve its durability.